Modeling of Strain Actuation on Relatively Soft Curved Beams by Piezoelectric Ceramics for De-Icing Systems - Salvatore Ameduri; Armando Castrovinci; Alessia Serena Perna; Antonio Viscusi; Antonio Concilio; Luigi Carrino (Applied Sciences, 2023)
In this work, the effects of some geometric and mechanical parameters that characterize curved and relatively soft structures integrated with piezoelectric actuators are investigated. The effect of parameters such as the curvature, location, and extension of the piezo device, as well as the thickness of the bonding and its strength, are considered in view of a potentially lighter model that replaces the piezoelectric device via its actions, namely pin forces, whose layout and values are strongly dependent on the curvature. When comparing the results obtained by a finite element model of the structure with the piezo device and of the structure alone under the action of pin forces, dedicated indicators were found, which could be useful to support lighter modeling approaches and to predict the authority of the piezoelectric device.